The Creativity of Artificial Intelligence in Art - Mingyong Cheng (Proceedings, 2022)
New technologies, especially in the field of artificial intelligence, are dynamic in transforming creative space. AI-enabled programs are rapidly contributing to areas such as architecture, music, the arts, science, and so on. The recent Christie’s auction on the Portrait of Edmond has transformed the contemporary perception of AI art, giving rise to questions related to the creativity involved in this art. This research paper acknowledges the persistent problem, “Can AI art be considered as being creative?” In this light, this study draws on the various applications of AI, varied attitudes on AI art, and the processes of generating AI art to establish an argument that AI is capable of achieving artistic creativity.